Targeting cholesterol biosynthesis promotes anti-tumor immunity by inhibiting long noncoding RNA SNHG29-mediated YAP activation - Ni, Wen; Mo, Hui; Liu, Yuanyuan; Xu, Yuanyuan; Qin, Chao; Zhou, Yunxia; Li, Yuhui; Li, Yuqing; Zhou, Aijun; Yao, Su; Zhou, Rong; Huo, Jianping; et al. (Molecular therapy, 2021)
Anti-tumor immunity through checkpoint inhibitors, specifically anti-programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) interaction, is a promising approach for cancer therapy. However, as early clinical trials indicate that colorectal cancers (CRCs) do not respond well to immune-checkpoint therapies, new effective immunotherapy approaches to CRC warrant further study. Simvastatin is an inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A (CoA) reductase (HMGCR), the rate-limiting enzyme of the mevalonate (MVA) pathway for the cholesterol biosynthesis. However, little is known about the functions of simvastatin in the regulation of immune checkpoints or long noncoding RNA (lncRNA)-mediated immunoregulation in cancer. Here, we found that simvastatin inhibited PD-L1 expression and promoted anti-tumor immunity via suppressing the expression of lncRNA SNHG29. Interestingly, SNHG29 interacted with YAP and inhibited phosphorylation and ubiquitination-mediated protein degradation of YAP, thereby facilitating downregulation of PD-L1 transcriptionally. Patient-derived tumor xenograft (PDX) models and the clinicopathological analysis in samples from CRC patients further supported the role of the lncRNA SNHG29-mediated PD-L1 signaling axis in tumor microenvironment reprogramming. Collectively, our study uncovers simvastatin as a potential therapeutic drug for immunotherapy in CRC, which suppresses lncRNA SNHG29-mediated YAP activation and promotes anti-tumor immunity by inhibiting PD-L1 expression. [Display omitted] Ni et al. found that simvastatin suppresses lncRNA SNHG29-mediated YAP activation and promotes anti-tumor immunity by inhibiting PD-L1 expression, proposing simvastatin treatment as a potential therapy or an adjuvant therapy for immunotherapy in colorectal cancer.